Clinical trials using antisense oligonucleotides in duchenne muscular dystrophy. - Koo, T; Wood, M (2013)
Duchenne muscular dystrophy (DMD) is a severe muscle wasting disorder caused by mutations in the DMD gene, affecting 1 in 3500 newborn males. Complete loss of muscle dystrophin protein causes progressive muscle weakness and heart and respiratory failure, leading to premature death. Antisense oligonucleotides (AONs) that bind to complementary sequences of the dystrophin pre-mRNA to induce skipping of the targeted exon by modulating pre-mRNA splicing are promising therapeutic agents for DMD. Such AONs can restore the open reading frame of the DMD gene and produce internally deleted, yet partially functional dystrophin protein isoforms in skeletal muscle. Within the last few years, clinical trials using AONs have made considerable progress demonstrating the restoration of functional dystrophin protein and acceptable safety profiles following both local and systemic delivery in DMD patients. However, improvement of AON delivery and efficacy, along with the development of multiple AONs to treat as many DMD patients as possible needs to be addressed for this approach to fulfill its potential. Here, we review the recent progress made in clinical trials using AONs to treat DMD and discuss the current challenges to the development of AON-based therapy for DMD.